Analysis And Design Information System Library Based On Client-Server - Binanda A S; Purwanto I (International Conference on Engineering and Technology Development (ICETD), 2017)
The library is one of the means of resources in which there are a variety of information about science, technology and culture were very helpful student, students, employees and society in general to increase motivation to learn and find out about something. Progress of a library can be seen from how the library information system is also of the quality of services to its members party libraries. To give a good service, one of which is to increase the library became computerized information systems so that the computer-based work and the expected effectiveness of library services to members to be better. SMK Negeri 1 Ketapang is located in East JL.Lintas Trenches 8, Village Berundung Ketapang District of South Lampung regency. SMK Negeri 1 Ketapang start learning activities on July 17, 2008with opening the Skills Program are: Computer Network, Agribusiness Fisheries Processing Technology of Fisheries with the number of students 162 students, later in the year to 3rd open Expertise Program New namely Technology Light Vehicle with number of students 38 students, 4th year SMK 1 Ketapang re-open one of the new Department of Administration by the number of students 40 students, with increasing majors are expected to educate the younger generation that is more potent in successive fields each according to their expertise. Facilities and infrastructure in SMKNegeri 1 Ketapang is very adequate. One of them was a library that can support teaching and learning processes in every department.